Fiber sizing liquid, polyether-ether-ketone composite material and preparation method of polyether-ether-ketone composite material
By using polyaryletherketone containing imide side groups as fiber slurry, combined with carbon nanotubes and other additives, the problem of poor compatibility between PEEK thermoplastic resin matrix and thermosetting sizing agent fibers is solved, and the mechanical properties and heat resistance of the composite material are significantly improved.
Patent Information
- Application Number
- CN202411844812.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
AI Technical Summary
The fiber compatibility of PEEK thermoplastic resin matrix and the thermosetting sizing agent is poor, resulting in low interfacial shear strength of the composite material, and the thermosetting sizing agent degrades at high temperatures, affecting molding and mechanical properties.
Polyaryletherketone containing imide-sided groups is used as the main material for the fiber slurry, combined with carbon nanotubes, silane coupling agents and lubricants, and the compatibility and interface bonding performance of the fibers with PEEK are improved through heat treatment and melt blending and extrusion.
It significantly improves the interface compatibility and bonding performance between fiber and PEEK, improves the tensile strength and elongation of break of composite materials, and improves wear and heat resistance.
Smart Images

Figure BDA0005188908480000021 
Figure BDA0005188908480000022 
Figure BDA0005188908480000023
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a fiber sizing liquid, a polyetheretherketone composite material and a preparation method thereof. Background Art
[0002] Fiber-reinforced polymer composites are the main components of structural applications. In all these applications, epoxy resins, vinyl resins, polyamides, polyaryletherketones and other thermosetting polymers and thermoplastic polymers play an important role. In these composites, the fiber is the main load-bearing part, and the resin matrix plays the role of substrate and load transfer medium. Therefore, the interface performance becomes an important factor affecting the mechanical properties of the composite. In order to ensure the firmness of the interface, it is necessary to improve the compatibility between the fiber and the resin. The chemical inertness of the fiber surface is difficult to be infiltrated by the matrix resin or form a chemical bond with it. Therefore, most fibers undergo certain surface treatments during the manufacturing process to improve their compatibility with the resin, such as heat treatment, oxidation treatment, plasma treatment, high-energy ray irradiation treatment, sizing agent treatment, etc. Among them, the most common treatment method is sizing agent treatment. Compared with the above-mentioned fiber surface treatment methods, coating a layer of polymer sizing agent on the fiber surface to change the structure and properties of the composite interface layer not only improves the interface compatibility, but also does not damage the fiber. At the same time, it has the advantage of improving the interface bonding performance without sacrificing other in-plane mechanical properties.
[0003] Only when the compatibility between the sizing agent and the resin matrix is good can the fiber composite material play its due performance. Most of the commercially available fibers use thermosetting sizing agents such as epoxy resin, which are often suitable for thermosetting resin matrices that are compatible with them. When they are used in PEEK thermoplastic resin matrices, there are often the following problems: PEEK has a rigid and stable structure, lacks active functional groups and is not easy to react with other active groups, and has poor compatibility or incompatibility with the fiber of the thermosetting sizing agent, resulting in low interfacial shear strength of the composite material; the PEEK processing and molding temperature exceeds 250°C, while the use temperature of the thermosetting sizing agent is generally lower than this temperature. When the temperature exceeds this temperature, the thermosetting sizing agent will degrade and release gas, which seriously affects the molding of the composite material; when the fiber of the thermosetting sizing agent is used for PEEK, its thermal stability is poor when used for a long time at high temperature, which will have an adverse effect on the mechanical properties of the fiber composite material. Summary of the invention
[0004] In order to solve the above technical problems, a fiber sizing solution, a polyetheretherketone composite material and a preparation method thereof are provided. The sizing solution of the present invention can effectively improve the compatibility between the fiber and PEEK, so that the mechanical properties of the composite material are improved.
[0005] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0006] A fiber sizing solution, comprising the following materials by weight: 6-10 parts of polyaryletherketone containing imide side groups, 0.1-2 parts of carbon nanotubes, 0.1-2 parts of silane coupling agents, 0.1-2 parts of lubricants, and at least 70 parts of organic solvents; and the mass concentration of the fiber sizing solution is at least 5wt%;
[0007] The chemical structure of the polyaryletherketone containing imide side groups is as follows:
[0008]
[0009] x = 1 or 2; and There is no X group (i.e., a biphenyl structure), or the X group is one of the following groups:
[0010]
[0011] in It represents the connecting bond connecting the two benzene rings with imide side groups on the left and right sides;
[0012] n represents the degree of polymerization, and the polyaryletherketone containing imide side groups is a low molecular weight polymer with a number average molecular weight of 10,000 g / mol-15,000 g / mol. When the molecular weight exceeds this range, it has a large viscosity after being dissolved in an organic solvent at room temperature and requires a relatively large amount of organic solvent.
[0013] Furthermore, the chemical structure of the polyaryletherketone containing imide side groups is as follows:
[0014]
[0015] The polyaryletherketone compound containing an imide side group is obtained by polycondensing bisphenol AF containing an imide with 4,4'-difluorobenzophenone with reference to the related invention CN202411516988.7. The structure of the bisphenol AF containing an imide is as follows:
[0016] This is specifically described in the related invention CN202411516988.7.
[0017] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes (MWCNTs) with a diameter greater than 5 nanometers and an aspect ratio ranging from 50-100.
[0018] Further, the silane coupling agent is selected from one or more of bis-(γ-triethoxysilylpropyl) tetrasulfide, vinyl tri(β-methoxyethoxy) silane, γ-glycidylpropyl-trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane; preferably, the silane coupling agent is selected from a compound of vinyl tri(β-methoxyethoxy) silane or γ-methacryloxypropyl trimethoxysilane and bis-(γ-triethoxysilylpropyl) tetrasulfide, and the two are in equal mass ratio. The preferred silane coupling agent is a high temperature resistant coupling agent with a high thermal decomposition temperature.
[0019] Furthermore, the lubricant is one or more of silicone powder, stearic acid amide, calcium stearate, and zinc stearate; preferably, the lubricant is a composite of calcium stearate or zinc stearate and silicone powder, and the mass ratio of the two is 1:2-5.
[0020] Furthermore, the organic solvent is one or more of dichloromethane, dichloroethylene, benzene, toluene, ethylbenzene, xylene, naphthalene, ethyl acetate, N,N-dimethylformamide (DMF), N,N-dimethylformamide (DMAc), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO).
[0021] The preparation and addition order of the fiber sizing liquid is: first dissolve the silane coupling agent in the organic solvent, add the carbon nanotubes after stirring evenly, continue to stir evenly, add the lubricant, continue to stir evenly, and finally add the polyaryletherketone containing imide side groups and adjust the concentration of the fiber sizing agent, and mix evenly.
[0022] Another aspect of the present invention provides a method for preparing a polyetheretherketone composite material, comprising the following steps:
[0023] S1, heat treatment to remove the original sizing agent on the fiber surface, re-sizing the fiber with the fiber sizing solution of the polyaryletherketone containing imide side groups of the present invention, stirring for a period of time, draining, and drying to obtain sized fibers;
[0024] S2, melt-blending and extruding the sizing fiber and polyetheretherketone, and granulating or compression molding to obtain a polyetheretherketone composite material.
[0025] Furthermore, the fiber is selected from one or more of carbon fiber (including chopped carbon fiber and continuous carbon fiber), glass fiber, basalt fiber, ceramic fiber, aramid fiber and polyimide fiber.
[0026] Furthermore, the heat treatment temperature is above 250°C until the fiber mass reaches a constant weight. However, if organic fiber is selected, the upper limit of the heat treatment temperature is less than the thermal decomposition temperature of the organic fiber. The melt blending temperature is 340-375°C.
[0027] Further, the fiber is immersed in the fiber sizing solution to be re-sized, the immersion time is 5-60 minutes, the re-sizing process is carried out at room temperature or at a temperature not exceeding 80° C., and after being controlled to dry, the immersion-drying process can be repeated multiple times to repeat the sizing;
[0028] The sizing rate of the fiber sizing liquid on the sized fiber is at least 0.5%. The attachment amount of the fiber sizing liquid can be controlled by the concentration of the sizing liquid and the soaking time, and the sizing can be repeated.
[0029] The last aspect of the present invention provides a polyetheretherketone composite material obtained by the above-mentioned preparation method. The polyetheretherketone composite material includes sizing fibers and polyetheretherketone. The sizing fibers account for 10%-35% of the composite material, and the polyetheretherketone accounts for at least 60%. Other functional additives may also be included and added as needed.
[0030] Beneficial technical effects: The present invention uses polyaryletherketone containing imide side groups as the main material of the sizing liquid. The polyaryletherketone containing imide side groups has a similar structure to polyetheretherketone, and the polyaryletherketone containing imide side groups has good compatibility with polyetheretherketone; the imide side groups form hydrogen bonds with the fiber surface, which plays a role of high adhesion. Although a higher fluorine content (usually more than 25%) can improve the interfacial adhesion, the large-volume imide side groups can compensate for the adverse effects of interfacial adhesion caused by the reduction of fluorine content, and can cooperate with a very small amount of fluorine elements to play a higher adhesion role; in addition, the silane coupling agent synergistically plays the effect of adhesion and affinity on the fiber, and the carbon nanotubes as a reinforcing material effectively improve the interfacial compatibility between the fiber and PEEK; the lubricant improves the interfacial performance, reduces the friction between the fiber and PEEK, improves the interfacial performance, and improves the wear resistance and heat resistance of the composite material;
[0031] The present invention improves the interfacial bonding performance between the fiber and the PEEK base material and can improve the problem of reduced toughness of the composite material, solves the problem of poor compatibility and uneven dispersion of the fiber and PEEK, and improves the tensile strength and elongation at break of the fiber-modified PEEK composite material. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0034] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0035] Preparation Example 1
[0036] The imide-containing bisphenol AF (see Example 1 of CN202411516988.7) and 4,4'-difluorobenzophenone are polycondensed to obtain a bisphenol AF type polyaryletherketone containing an imide side group, and the reaction process is as follows:
[0037]
[0038] In a 1000mL three-necked flask equipped with a mechanical stirrer, nitrogen inlet and outlet, water separator and reflux condenser, add 62.65g (0.1mol) of bisphenol AF containing imide, 21.82g (0.1mol) of 4,4'-difluorobenzophenone, 18.0g (0.13mol) of anhydrous K2CO3, 235g of DMF and 25mL of toluene. Under N2 atmosphere, stir at 60°C until the solid material is completely dissolved. After stirring and heating at 140°C for 2h, the generated water azeotropes with toluene, and the azeotropes are removed through the water separator. Then, the polymerization reaction is continued at 160-170° C. with stirring for 2-4 hours to obtain a viscous mixed solution; the viscous mixed solution is poured into a mixed solution of 600 mL of ethanol and water (volume ratio of 1:1) to precipitate a polymer; the mixture is soaked in a hot ethanol-water solution (volume ratio of ethanol to water of 1:2, temperature of 80° C.) for 30 minutes, repeated three times, and filtered and dried to obtain a bisphenol AF type polyaryletherketone containing imide side groups (hereinafter abbreviated as PI-PAEK).
[0039] The specific polymerization reaction conditions are as follows:
[0040] PI-PAEK-Ⅰ: The polymerization reaction was continued at 160°C with stirring for 3.5 hours. The number average molecular weight of the final product was 11,500 g / mol as determined by GPC.
[0041] PI-PAEK-Ⅱ: The polymerization reaction was continued at 170°C with stirring for 2.5 hours. The number average molecular weight of the final product was 13,900 g / mol as determined by GPC.
[0042] Preparation Example 2
[0043] This case is the preparation of fiber sizing solution, and the fiber sizing solution formula is shown in Table 1 below.
[0044] Slurry preparation process: first dissolve the silane coupling agent in DMF, stir evenly, then add MWCNTs, continue to stir evenly, add lubricant, continue to stir evenly, finally add polyaryletherketone PI-PAEK containing imide side groups and adjust the concentration of fiber sizing agent, and mix well.
[0045] Table 1 Sizing liquid formula
[0046]
[0047] Example 1-Example 10
[0048] A method for preparing a polyetheretherketone composite material comprises the following steps:
[0049] S1. The chopped carbon fibers were heat treated at 400°C to remove the original epoxy sizing agent on the surface, and the chopped carbon fibers were treated until the mass of the chopped carbon fibers was constant. After cooling, 2 kg of the chopped carbon fibers were immersed in 10 L of sizing solution (sizing solutions ①-⑩ in Table 1, see Table 2 for details) and stirred for 10 min. The solid materials were then drained and dried through ventilation for 2 h. The chopped carbon fibers were then transferred to a drying device and gradually heated to 200°C and dried to constant weight to obtain sizing chopped carbon fibers.
[0050] The sizing liquid used and the sizing attachment amount in the sized chopped carbon fibers are shown in Table 2;
[0051] S2, melt-blending and extruding the sizing fibers and polyetheretherketone at 350-375° C. to obtain a polyetheretherketone composite material. The sizing fiber content in the chopped carbon fiber / polyetheretherketone composite material is 30 wt%. The mechanical properties of the composite material are shown in Table 2.
[0052] Comparative Example 1
[0053] The preparation process of the composite material in this case is the same as that in Example 2, except that the chopped carbon fiber is not re-sized after heat treatment at above 400°C, but is directly melt-blended and extruded and granulated with polyetheretherketone to maintain the chopped carbon fiber content in the composite material at 30wt%. The properties are shown in Table 2.
[0054] Comparative Example 2
[0055] The preparation process of the composite material in this case is the same as that in Example 2, except that the sizing liquid after heat treatment is the one in Table 1. The performance is shown in Table 2.
[0056] Comparative Example 3
[0057] The preparation process of the composite material in this case is the same as that in Example 2, except that the sizing liquid after heat treatment is the one in Table 1. The performance is shown in Table 2.
[0058] Embodiment 11
[0059] The preparation process of the composite material in this case is the same as that in Example 10, except that glass fiber is used to replace the chopped carbon fiber. The properties are shown in Table 3.
[0060] Comparative Example 4
[0061] The preparation process of the composite material in this case is the same as that in Example 11, except that the glass fiber is not re-sized after heat treatment but is directly melt-blended with polyetheretherketone and extruded into granules. The properties are shown in Table 3.
[0062] Example 12
[0063] The preparation process of the composite material in this case is the same as that in Example 10, except that continuous carbon fiber is selected to replace short-cut carbon fiber. The properties are shown in Table 3.
[0064] Comparative Example 5
[0065] The preparation process of the composite material in this case is the same as that in Example 12, except that the continuous carbon fiber is not re-sized after heat treatment but is directly melt-blended with polyetheretherketone for extrusion granulation. The properties are shown in Table 3.
[0066] The above cases were tested for performance, and the specific results are shown in Table 2 and Table 3.
[0067] Table 2 Sizing fiber and composite material properties of Example 1-Example 10 and Control 1-Control 3
[0068]
[0069]
[0070] Table 3 Sizing fiber and composite material properties of Example 10-Example 12, Comparative Example 1, Comparative Example 4-Comparative Example 5
[0071]
[0072] It can be seen from Example 2 and Control Examples 1 to 3 in Table 2 that the sizing solution of Control Example 3 contains only bisphenol AF type polyaryletherketone containing imide side groups, and after the fiber is re-sized, the mechanical properties of the composite material can be greatly improved compared with Control Example 1; while Control Example 2 does not contain bisphenol AF type polyaryletherketone containing imide side groups, and the sizing solution only contains other auxiliary substances, and the positive effect on both the adhesion of the fiber and the improvement of the mechanical properties of the composite material is not obvious.
[0073] The present invention uses polyaryletherketone containing imide side groups as the main material of the sizing liquid. The polyaryletherketone containing imide side groups has a similar structure to polyetheretherketone, and the polyaryletherketone containing imide side groups has good compatibility with polyetheretherketone; the imide side groups form hydrogen bonds with the fiber surface, which play a role of high adhesion. Although a higher fluorine content (usually more than 25%) can improve the interface adhesion, the large-volume imide side groups can compensate for the adverse effect of interface adhesion caused by the reduction of fluorine content, and can cooperate with a very small amount of fluorine element to play a higher adhesion role; in addition, the silane coupling agent synergistically plays the effect of adhesion and affinity on the fiber (the effect of the auxiliary substance alone is not obvious), and the multi-walled carbon nanotubes are used as reinforcing materials to effectively improve the interface compatibility between the fiber and PEEK and improve the mechanical properties. The present invention improves the interfacial bonding performance between the fiber and the PEEK base material and can improve the problem of reduced toughness of the composite material, solves the problem of poor compatibility and uneven dispersion of the fiber and PEEK, and improves the tensile strength and elongation at break of the fiber-modified PEEK composite material.
[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A fiber sizing solution, characterized in that: The invention comprises the following materials by weight: 6-10 parts of polyaryletherketone containing imide side groups, 0.1-2 parts of carbon nanotubes, 0.1-2 parts of silane coupling agent, 0.1-2 parts of lubricant, and at least 70 parts of organic solvent; and the mass concentration of the fiber sizing solution is at least 5wt%; The chemical structure of the polyaryletherketone containing imide side groups is as follows: x = 1 or 2; and There is no X group (i.e., a biphenyl structure), or the X group is one of the following groups: in It represents the connecting bond connecting the two benzene rings with imide side groups on the left and right sides; n represents the degree of polymerization, and the polyaryletherketone containing imide side groups is a low molecular weight polymer, and its number average molecular weight is 10,000 g / mol-15,000 g / mol.
2. A fiber sizing solution according to claim 1, characterized in that: The chemical structure of the polyaryletherketone containing imide side groups is as follows:
3. A fiber sizing solution according to claim 2, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a diameter greater than 5 nanometers and an aspect ratio ranging from 50 to 100.
4. A fiber sizing solution according to claim 2, characterized in that: The silane coupling agent is selected from one or more of bis-(γ-triethoxysilylpropyl) tetrasulfide, vinyl tris(β-methoxyethoxy)silane, γ-glycidylpropyl-trimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; The lubricant is one or more of silicone powder, stearic acid amide, calcium stearate, and zinc stearate; The organic solvent is one or more of dichloromethane, dichloroethylene, benzene, toluene, ethylbenzene, xylene, naphthalene, ethyl acetate, N,N-dimethylformamide, N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide.
5. A fiber sizing solution according to claim 4, characterized in that: The silane coupling agent is selected from a compound of vinyl tri(β-methoxyethoxy)silane or γ-methacryloxypropyl trimethoxysilane and bis-(γ-triethoxysilylpropyl) tetrasulfide, with the two having an equal mass ratio; The lubricant is a compound of calcium stearate or zinc stearate and silicone powder, and the mass ratio of the two is 1:2-5.
6. A method for preparing a polyetheretherketone composite material, characterized in that: The steps include: S1. removing the original sizing agent on the fiber surface by heat treatment, re-sizing the fiber with the fiber sizing solution according to any one of claims 1 to 5, stirring, draining, and drying to obtain sized fiber; S2, melt-blending and extruding the sizing fiber and polyetheretherketone, and granulating or compression molding to obtain a polyetheretherketone composite material.
7. The method for preparing a polyetheretherketone composite material according to claim 6, characterized in that: The fiber is selected from one or more of carbon fiber, glass fiber, basalt fiber, ceramic fiber, aramid fiber, and polyimide fiber; The temperature of the heat treatment is above 250°C until the fiber mass is constant; the temperature of the melt blending is 340-375°C.
8. The method for preparing a polyetheretherketone composite material according to claim 6, characterized in that: The fiber is immersed in the fiber sizing solution to be re-sized, the immersion time is 5-60 minutes, and the re-sizing process is carried out at room temperature or a temperature not exceeding 80° C.; The fiber sizing liquid has a sizing rate of at least 0.5% on the sized fibers.
9. A polyetheretherketone composite material, characterized in that: The polyetheretherketone composite material obtained by the preparation method according to any one of claims 6 to 8 comprises sizing fibers and polyetheretherketone, wherein the sizing fibers account for 10% to 35% of the composite material, and the polyetheretherketone accounts for at least 60%.
Citation Information
Patent Citations
Polyaryletherketone resin containing imide side group and preparation method of polyaryletherketone resin
CN119390967A
Cited By
Modified polybenzimidazole alloy and preparation method thereof
CN120574474A
A modified polybenzimidazole alloy and a method for preparing the same
CN120574474B
High-temperature-resistant water-based sizing agent as well as preparation method and application thereof
CN122103571A